Potensi Cangkang Udang Laut (Penaeus monodon F.) Terhadap Profil Lipid Tikus Putih Hiperlipidemia - Isdadiyanto, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
The objective of this study was to analyze the potency of sea shrimp carapace (Penaeus monodon F.) on lipid profiles of Sprague Dawley rats induced by high fat ration. The animals for this study were twenty adult male rats divided into four groups, i.e. group I as the control was fed with basal ration containing normal fat for 3 months, group II was fed ration containing high fat for 3 months, group III was fed ration containing high fat and given sea shrimp carapace 180 mg per kg body weight per day orally in 2 ml aquadest for 3 months, group IV was fed ration containing high fat for 3 months and after 1 month given sea shrimp carapace 180 mg per kg body weight per day orally in 2 ml aquadest for 2 months. Each group consisted of five animals. After 90 days, the rats were necropsied and the blood were collected to analyzes lipid profiles. Lipid profiles were measured using colorimetric enzymatic method and Roche/Hitachi cobas c systems automatically calculate. Â The difference between treatments was statistical analysis by Anava, and continued by Lowest Significant Difference Test to locate the difference. The result showed that high fat diet decreased HDL level, but increased total cholesterol level and LDL level. Sea shrimp carapace increased HDL but decreased total cholesterol level and LDL level in rats by high fat induction. Â Keywords: Sea shrimp carapace, Sprague Dawley rats, lipid profiles